Wide-scale subdivision and fencing of southern Kenyan rangelands jeopardizes biodiversity conservation and pastoral livelihoods: Demonstration of utility of open-access landDX database - Tyrrell, Peter; Buitenwerf, Robert; Brehony, Peadar; Løvschal, Mette; Wall, Jake; Russell, Samantha; Svenning, Jens-Christian; Macdonald, David W.; du Toit, Johan T.; Kamanga, John (Frontiers in Conservation Science, 2022)
Globally, rangelands are undergoing rapid social-ecological changes, yet the scale of these changes is rarely measured. Fencing, sedentarisation, and land conversion limit access by wildlife and livestock to vital resources such as water and seasonal forage, leading to rangeland degradation. In addition, these changes limit connectivity between wildlife sub-populations, triggering a spiral of decreasing biodiversity and weakening ecosystem function. Moreover, the combination of land privatisation, sedentarisation and fencing endangers pastoral livelihoods by reducing resilience to drought and diminishing livestock holdings per person. We provide a unique, urgent, and vital snapshot across >30,000 km2 of southern Kenya’s rangeland, covering four ecosystems renowned for their rich megafauna and pastoral people. We document and explore the drivers of extensive fencing (~40,000 km), the proliferation of livestock enclosures (>27,000), and the conversion of rangelands for cultivation (~1,500 km2). Fencing is generally more prolific in areas that have been converted from community tenure to private title, especially where land values are raised by agricultural potential and proximity to Kenya’s capital, Nairobi. Space for wildlife (and traditional pastoralism) is limited on private, subdivided land where livestock enclosures are at their highest density and where there is less unfenced and untransformed land between than within conservation areas and pastoral commons. Conflicting planning incentives, policies, and economic forces are driving unsustainable and potentially irreversible social-ecological transitions at unprecedented scales. The lesson from southern Kenya is that a range of financial, policy and governance-related interventions are required to allow people and nature to coexist sustainably in African savannas.